2001
DOI: 10.1016/s0014-5793(01)03124-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel second myostatin gene is present in teleost fish

Abstract: We report on the isolation and characterisation of the complete cDNA sequence encoding a novel bone morphogenetic protein-like protein (sbMSTN-b) in the teleost fish Sparus aurata. The encoded protein is 68% identical to S. aurata MSTN at the amino acid level, and homologues were also found in Umbrina cirrosa and Tetraodon nigroviridis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 22 publications
3
52
1
Order By: Relevance
“…Although cDNA clones have been characterized in many diverse fish species (Ostbye et al 2001, Roberts & Goetz 2001, Rescan et al 2001, Maccatrozzo et al 2001a, Kocabas et al 2002, Kerr et al 2005, very few genes have been completely characterized. This is particularly disconcerting since bony fish, especially teleosts, represent the largest group of extant vertebrates and many of these species are commercially important.…”
Section: Introductionmentioning
confidence: 99%
“…Although cDNA clones have been characterized in many diverse fish species (Ostbye et al 2001, Roberts & Goetz 2001, Rescan et al 2001, Maccatrozzo et al 2001a, Kocabas et al 2002, Kerr et al 2005, very few genes have been completely characterized. This is particularly disconcerting since bony fish, especially teleosts, represent the largest group of extant vertebrates and many of these species are commercially important.…”
Section: Introductionmentioning
confidence: 99%
“…MSTN-1 and MSTN-2 [8][9][10] . In transgenic Coho Salmon that over-expressed growth hormone (GH), MSTN-1 transcription level was not altered in muscle or brain, compared with wild-type adult Coho Salmon.…”
Section: Discussionmentioning
confidence: 99%
“…MSTN-1 in S. aurata is expressed in muscle as well as in several other tissues, such as brain, eyes, intestine, kidney and heart, while MSTN-2 is expressed mainly in brain, including the olfactory and optic lobes [9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the blockade of myostatin produces larger specimens of zebrafish (Danio rerio) and rainbow trout (Oncorhynchus mykiss), due to elevation of muscle hypertrophy and hyperplasia processes [30][31][32][33]. Myostatin has been isolated and characterized in several fish species [29,[34][35][36][37][38][39][40]. In the present work, we have investigated the morphological characteristics and the expression of growth-related factors in skeletal muscle of pirarucu during growth.…”
Section: Introductionmentioning
confidence: 99%